Linear programming model for optimizing of noise and vibration in passenger car cabin - Ahmad Kadri, Junoh; Z. M., Nopiah; Wan Zuki Azman, Wan Muhamad; Najah, Ghazali; Noor Adila, Aluwi Shakir; Mohd Jailani, Mohd Nor, Prof. Dr.; Mohammad, Hosseini Fouladi (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/